From bargaining power to empowerment: Measuring the unmeasurable - Quisumbing, Agnes R. (International Association of Agricultural Economists, 2024)
Measuring power is central to empirical work on intrahousehold and gender relations. Early efforts to test household models focused on measuring spousal bargaining power, usually in models featuring two decisionmakers within the household. Proxy measures for bargaining power included age, education, assets, and “outside options” that could affect spouses’ threat points within marriage. Evidence rejecting the collective model of the household has influenced the design of policies and programs, notably conditional cash transfer programs. Efforts have since shifted to measuring empowerment, drawing on theories of agency and power. Since 2010, several measures of women’s empowerment have been developed, including the Women’s Empowerment in Agriculture Index (WEAI) and its variants. A distinct feature of the WEAI, like other counting-based measures, is its decomposability into its component indicators, which makes identifying sources of disempowerment possible. The WEAI indicators also embody jointness of decision-making or ownership, which better reflects actual decision-making within households compared to 2-person bargaining models. This paper reviews how progress in the measurement of power within households has facilitated our understanding of household decision-making and creates new opportunities for programs and policy.